2010
DOI: 10.1177/1046496409357081
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Environment and Outcomes in a U.K. Domestic Violence Perpetrator Program

Abstract: This study examines the extent to which variations in program delivery affect the therapeutic environment and whether the therapeutic environment is associated with psychological and behavioral outcomes in a domestic violence perpetrator program. Seventy-seven offenders and 31 probation group tutors participated. It was found that groups with longer sessions were perceived more favorably by offenders than those with shorter sessions. A positive correlation was identified between group organization and offender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Por otra parte, en futuros estudios de evaluación de programas dirigidos a maltratadores debe plantearse el marco de intervención como variable relevante (Bowen, 2010) y considerar que los resultados pueden diferir en función de aspectos como el tipo delictivo, la obligatoriedad, la motivación o las expectativas puestas en el tratamiento. En este sentido, deberán mejorarse las estrategias que aumenten la motivación, la alianza terapéutica y la adherencia de los hombres al tratamiento (Dia, Simmons, Oliver y Cooper, 2009;Maiuro y Murphy, 2009;Musser, Semiatin, Taft y Murphy, 2008;Taft y Murphy, 2007) en un contexto que inicialmente puede quedar definido como no terapéutico (Cirillo, 1994).…”
Section: Discussionunclassified
“…Por otra parte, en futuros estudios de evaluación de programas dirigidos a maltratadores debe plantearse el marco de intervención como variable relevante (Bowen, 2010) y considerar que los resultados pueden diferir en función de aspectos como el tipo delictivo, la obligatoriedad, la motivación o las expectativas puestas en el tratamiento. En este sentido, deberán mejorarse las estrategias que aumenten la motivación, la alianza terapéutica y la adherencia de los hombres al tratamiento (Dia, Simmons, Oliver y Cooper, 2009;Maiuro y Murphy, 2009;Musser, Semiatin, Taft y Murphy, 2008;Taft y Murphy, 2007) en un contexto que inicialmente puede quedar definido como no terapéutico (Cirillo, 1994).…”
Section: Discussionunclassified
“…For example, even though the majority of the studies stated the use of a quasi-experimental design, in fact the design was not a quasi-experimental one 26,29,30,[33][34][35]37,39,64 . This happens because among the identified studies were found: (i) studies without a control group 29,33,35,40 ; (ii) studies that assessed the effectiveness after the ending of the treatment (post-test design) 36,45,48 ; (iii) studies that used measures in the pre-and post-test (pre-post-test designs) 29,30,31,37,38,40 ; and (iv) studies with a non-equivalent control group 20,27,31 . Moreover, the programs without a control group did not provide a reference point in order to assess their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the proliferation and expansion of intervention programs for batterers, different studies have produced variable and contradictory results. If, on one hand, some programs show positive results 26,27,32,33,35,37,39,43,47 , others do not reveal significant differences between the group that participated in the intervention and the group that did not receive intervention 20,28,42,52,54 . Some authors state that mixed results are due to either differences in terms of indicators and measures used in the assessment 17,22,66,65 or the success and efficacy definition 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate question was whether characteristics of the talk and interaction could give indications of the abstract phenomena of the working alliance or therapeutic environment (see Bowen, 2010).…”
Section: Dialogues In Partner Abusive Clients' Group 26mentioning
confidence: 99%
“…Bowen, 2010;Eckhardt et al, 2004;Scott, 2004). This has led to an increasing interest in qualitative process factors such as (the characteristics of) client motivation, program delivery, the group environment, group integrity/cohesion, the working style of group counselors, and the working alliance between clients and counselors.…”
mentioning
confidence: 99%